Scientific Prediction of the Covid-19 Pandemic and What Should Society Do? - Iche Andriyani Liberty; Mariatul Fadilah; Hari Kusnanto Josef (Faculty of Medicine, Public Health, and Nursing, 2020)
What is the scientific prediction for the Covid-19 pandemic? Currently, as of April 8, the world’s confirmed cases have over 1.2 million, the death of more than 72 thousand. For Indonesia, today 2,738 confirmed cases, 221 deaths, and those who recovered 204.1-3. The update on April 8 today, WHO itself estimates that the Covid-19 Contagion Rate is 1.4 to 2.5. This will form the basis of predictive modeling. Several studies conducted show that currently the basic reproduction number or R0 of Covid-19 is higher than SARS. Initially in the range of 2-3 or an average of 2.5, currently R0 is 1.4 - 6.9. This is what will form the basis of modeling. R0 or the basic reproduction number shows how many people a person can become infected with. If the R0 is more than 1, we are in an epidemic status as it is today, R0 = 1 endemic, and our R0 is less than 1 we have eradicated. R0 itself consists of three components, namely p: transmission, c: number of contact, and D which is the duration of the infection itself. These calculations are the main points in modeling.